Effects of reproduction on sexual dimorphisms in rat bone mechanics. (22nd August 2018) - de Bakker, Chantal M.J.; Zhao, Hongbo; Tseng, Wei-Ju; Li, Yihan; Altman-Singles, Allison R.; Liu, Yang; Leavitt, Laurel; Liu, X. Sherry
Abstract: Osteoporosis most commonly affects postmenopausal women. Although men are also affected, women over 65 are 6 times more likely to develop osteoporosis than men of the same age. This is largely due to accelerated bone remodeling after menopause; however, the peak bone mass attained during young adulthood also plays an important role in osteoporosis risk. Multiple studies have demonstrated sexual dimorphisms in peak bone mass, and additionally, the female skeleton is significantly altered during pregnancy/lactation. Although clinical studies suggest that a reproductive history does not increase the risk of developing postmenopausal osteoporosis, reproduction has been shown to induce long-lasting alterations in maternal bone structure and mechanics, and the effects of pregnancy and lactation on maternal peak bone quality are not well understood. This study compared the structural and mechanical properties of male, virgin female, and post-reproductive female rat bone at multiple skeletal sites and at three different ages. We found that virgin females had a larger quantity of trabecular bone with greater trabecular number and more plate-like morphology, and, relative to their body weight, had a greater cortical bone size and greater bone strength than males. Post-reproductive females had altered trabecular microarchitecture relative to virgins, which was highly similar to that of male rats, and showed similar cortical bone size and bone mechanics to virgin females. This suggests that, to compensate for future reproductive bone losses, females may start off with more trabecular bone than is mechanically necessary, which may explain the paradox that reproduction induces long-lasting changes in maternal bone without increasing postmenopausal fracture risk.